Interconnections Among Linguistics, Sociolinguistics, and Forensic Linguistics in Legal Contexts: a Qualitative Literature Review - Rezki Amalia Wahyuni Mustakim; Fitri Arniati; Muh. Syahrul Ago; Nurlely Nasaruddin; Hendrik Johan Posuma (Universitas Islam Negeri Palopo, 2026)
Language-related questions in legal settings require an analysis that connects linguistic form with social context and institutional meaning. This conceptual study examines the interconnections among general linguistics, sociolinguistics, and forensic linguistics and explains their relevance to legal analysis. It employs a qualitative descriptive design and a literature review of books, journal articles, and other academic sources concerning the three fields. The sources are synthesized conceptually to identify their principal objects of analysis, areas of contribution, and relationships within legal contexts. The review identifies four connected themes. First, linguistics provides analytical tools for examining language structure, meaning, and use. Second, sociolinguistics explains how identity, social relationships, language variation, power, and communicative context influence language choices. Third, forensic linguistics applies these insights to legal texts, disputed authorship, recorded interaction, and the interpretation of potentially ambiguous or harmful expressions. Fourth, sociolinguistic context is necessary to reduce decontextualized interpretations of linguistic evidence. The analysis indicates that linguistic evidence is most informative when structural features are considered together with speaker relationships, communicative circumstances, and institutional norms. Nevertheless, linguistic analysis should support rather than replace broader legal evaluation because language interpretation is context-dependent and may involve uncertainty. The study offers a concise conceptual framework for understanding the complementary roles of the three fields in legal settings